RISIKO, PROFITABILITAS, LEVERAGE OPERASI, DAN UKURAN PERUSAHAAN TERHADAP PERATAAN LABA - Syafriont By (Jurnal Keuangan dan Perbankan, 2008)
A recent analysis showed that there was a significant effect among firm size,corporate risk, profitability and operating leverage to corporate income smoothing practices.The objective of this research was to empirically reexamine the factors that affected incomesmoothing practices. There were four factors that were examined, namely firm size, corporaterisk, profitability and operating leverage. The samples used in this study were 89 firms listedat Indonesian Stock Exchange (ISE between 2005 to 2007). The multivariate test, the use oflogistic regression results showed both risk and profitability affected significantly to incomesmoothing practices. While firm size and operating leverage did not affect significantly toincome smoothing practices, the univariate test support the previous test that showed therewas statistically difference in risk as well as profitability between smoother and non-smootherfirms. However, both firm size and operating leverage were not statistically different.